O dziecięcej tożsamości (tragicznie) zerwanej – gdy przemoc symboliczna może życie ocalić - Maria Szczepska-Pustkowska; Małgorzata Lewartowska-Zychowicz; Longina Strumska-Cylwik (Problemy Wczesnej Edukacji)
The presented text aims, on the one hand, to recall people’s lives that should not be forgotten, and on the other hand, it is an attempt to mark in their context the borderline of the validity of contemporary pedagogical reflection on symbolic violence. The former concerns the analysis of Polish Jews’ childhood experiences from the World War II period, connected with the breaking of the primary national and religious identity and re-integration into a new Polish identity. The latter aim is related to the embedding of the indicated problem on the background of contemporary pedagogical reflection, and in particular critical pedagogy, for which one of the key categories has become symbolic violence, aimed at changing the human identity. The goal is to analyze the children’s testimonies of the Holocaust, in which the theoretical concept of the enslaved childhood of Wiesław Theiss was used. It allowed to capture the field of enslavement of Jewish children in its various dimensions.